2014
DOI: 10.1371/journal.pone.0086344
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Biochemical Analyses Revealed a Detailed Proanthocyanidin Biosynthesis Pathway in Brown Cotton Fiber

Abstract: Brown cotton fiber is the major raw material for colored cotton industry. Previous studies have showed that the brown pigments in cotton fiber belong to proanthocyanidins (PAs). To clarify the details of PA biosynthesis pathway in brown cotton fiber, gene expression profiles in developing brown and white fibers were compared via digital gene expression profiling and qRT-PCR. Compared to white cotton fiber, all steps from phenylalanine to PA monomers (flavan-3-ols) were significantly up-regulated in brown fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 32 publications
2
76
0
Order By: Relevance
“…Fiber color is conferred by the accumulation of flavonoids in mature fibers (Hua et al 2007;Xiao et al 2007Xiao et al , 2014Li et al 2012a;Feng et al 2013;Tuttle et al 2015). Thirteen QTL were detected for the three fiber color traits evaluated: mean L * (bright/dark), mean a * (green/red), and mean b * (blue/yellow).…”
Section: Fiber Colormentioning
confidence: 99%
“…Fiber color is conferred by the accumulation of flavonoids in mature fibers (Hua et al 2007;Xiao et al 2007Xiao et al , 2014Li et al 2012a;Feng et al 2013;Tuttle et al 2015). Thirteen QTL were detected for the three fiber color traits evaluated: mean L * (bright/dark), mean a * (green/red), and mean b * (blue/yellow).…”
Section: Fiber Colormentioning
confidence: 99%
“…The cis-form and trans-form of flavan-3-ols were synthesized in LAR and ANR branches, respectively [11,38,58,72]. Mass spectrometry (MS) analyses revealed that the main PA monomers in brown cotton fibers contained three hydroxyls on the B ring (gallocatechin or epigallocatechin) [11,21,73], PA accumulation in brown fibers starts at an early stage (5 DPA) and peaks at 30 DPA, PAs are gradually converted into oxidized derivatives (quinones) in mature brown fibers. Because developing brown fibers do not exhibit distinct coloration until maturation, the condensed quinones maybe directly contribute to brown pigmentation in cotton fibers instead of their PA precursors [11].…”
Section: The Anthocyanidins Content In the Fiber Directly Influenced mentioning
confidence: 99%
“…Over the past ten years, many studies have focused on the metabolic and transcriptional analyses and QTL mapping of brown cotton bers. Flavonoids were detected in the extractions of brown cotton bers (Hua et al 2007), and the avonoid biosynthesis pathway, especially proanthocyanidin (PA) biosynthesis, was activated during ber development of brown cottons (Feng et al 2013;Liu et al 2018;Tan et al 2013;Xiao et al 2014). QTL mapping found six genetic loci (Lc1, Lc2, Lc3, Lc4, Lc5 and Lc6) which were associated with ber colors of brown cottons, and further studies showed that GhTT2-3A(Gh_A07G2341), a gene controlling PA biosynthesis, was a candidate gene that was con rmed by transgenic analysis to control ber pigmentation of brown cotton (Hinchliffe et al 2016;Wen et al 2018;Yan et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore both metabolic and gene expression analyses showed that the pigments in brown cotton bers were PA or PA derivatives (Feng et al 2014;Xiao et al 2014;Yan et al 2018), while the pigments in green cotton bers remained uncertain. Some transcriptional and metabolic analyses supported the view that flavonoids and their derivatives were the dominant pigments in green cotton bers (Hua et al 2007;Liu et al 2018;Yuan et al 2012), but other analyses suggested that caffeoyl residues were related to pigmentation in these bers (Feng et al 2017;Ma et al 2015).…”
Section: Introductionmentioning
confidence: 99%